Penertiban Anak Jalanan Oleh Satuan Polisi Pamong Praja di Kota Balikpapan Provinsi Kalimantan Timur - Dendy Noer Alam; Dadang Supriatna (Fakultas Hukum Tata Pemerintahan, 2025)
The city of Balikpapan is one of the big cities which is the gateway to East Kalimantan Province and is the main city chosen by the people as a place to live. This makes urbanization in Balikpapan City high and has an impact on the increasing number of street children in Balikpapan City. The increasing number of street children is a problem that needs attention. Because its presence can disturb peace and public order in society. Therefore, it is necessary to take disciplinary action from the government, namely Satpol PP, to overcome this problem. The aim is to find out and describe the implementation of controlling street children and to find out what obstacles and efforts are made by Civil Service Police Units in the City of Balikpapan in carrying out control of street children in Balikpapan City, East Kalimantan Province. The research method used is qualitative descriptive using an inductive approach. Data collection techniques are through observation, interviews and documentation, by using Retno Widjayanti theory which includes; direct control and indirect control. From the research results, it can be seen that the control of street children has not been carried out optimally due to several obstacles such as lack of facilities and infrastructure, quality of human resources, economy and budget limitations. Several efforts have been made, such as routine patrol activities 3 times a day in the morning, afternoon and even during the day. Then update the reporting or complaint system so that information can be obtained quickly and accurately. As well as increasing the quality standards for recruiting Civil Service Police Units members and also requesting an additional budget for the Balikpapan City Satpol PP. The control of street children has not been carried out optimally because there are still many street children roaming around carrying out activities on the streets caused by internal and external factors.